TREATMENT OF WASTEWATER USING MFC - P. Shanmuganathan , P. Rajasulochana , A. Ramachandra Murthy (PalArch’s Journal of Archaeology of Egypt / Egyptology, 2020)
Microbial fuel cells are bioelectrochemical system where microrganisms acts as biocatalyst gaining metabolic energy by transferring electrons from an electron donor to an electron acceptor. A mediatorless microbial fuel cell was designed on naturally occurring E.coli in domestic wastewater, which directly transfers electrons with the help of pili and biofilms. Microaerophilic studies helps in steady state of electron transfer and the present study relies on comparing the efficiency of batch and continuous systems. The continuous mode systems were efficient in highest power production than the batch mode with Nafion 1135 as proton exchange system. The maximum voltage reported was 960 mV in domestic wastewater. The COD removal efficiency was found to be around 90% hence enables a better technology for wastewater treatment associated with power generation and biofuel production. Future aspects of MFCs are also discussed.